2023
DOI: 10.1029/2023gc010978
|View full text |Cite
|
Sign up to set email alerts
|

Highly Contrasted Geochemical Pattern in Sediments of the Okavango Delta, Botswana Driven by Dust Supply, Hydrological Heritage and Biogeochemical Reactions

Abstract: The Okavango Delta in North Botswana is one of the few active alluvial mega-fans developing in an endorheic setting (Assine & Soares, 2004;McCarthy, 2013) (Figure 1). This fan forms a vast swamp flooded annually by water from the highlands of Angola to the North and it supports an exceptional ecosystem in the middle of the semi-arid Kalahari Desert. Due to their isolation, endorheic ecosystems result from tight coupling between climatic, topographic and geologic settings. Changes in one or several of these con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 106 publications
1
22
0
Order By: Relevance
“…Samples containing high concentrations of CaO are enriched in REEs (Figure 2a) and exhibit clear fractionation of the Gd/Yb ratio (Figure 2b), reflecting the varying ability of REEs to incorporate into the solid phase (log D Gd = 3.4 vs. log D Yb = 1.9). We suggest that this process is responsible for the distinctive concave REE concentration patterns Jolivet et al (2023) observed in the island subsurface samples they analyzed. Rather than indicating the presence of two non-connected aquifers, the differing REE patterns observed in sediment samples from Nxaraga Island reflects the preferential fractionation of REEs into calcite, which precipitates as a consequence of evapotranspiration.…”
Section: Critique Of the Jolivet Et Al Modelmentioning
confidence: 77%
See 4 more Smart Citations
“…Samples containing high concentrations of CaO are enriched in REEs (Figure 2a) and exhibit clear fractionation of the Gd/Yb ratio (Figure 2b), reflecting the varying ability of REEs to incorporate into the solid phase (log D Gd = 3.4 vs. log D Yb = 1.9). We suggest that this process is responsible for the distinctive concave REE concentration patterns Jolivet et al (2023) observed in the island subsurface samples they analyzed. Rather than indicating the presence of two non-connected aquifers, the differing REE patterns observed in sediment samples from Nxaraga Island reflects the preferential fractionation of REEs into calcite, which precipitates as a consequence of evapotranspiration.…”
Section: Critique Of the Jolivet Et Al Modelmentioning
confidence: 77%
“…The implication of this is that large regions of the floodplain may revert to dry land and remain so for decades (McCarthy et al, 2003), during which time termites are able to colonize the dry surfaces. Jolivet et al (2023) and Dauteuil et al (2021) proposed that the groundwater beneath floodplains and islands are hydrologically separate. However, several studies have demonstrated there is a complete evolutionary link between fresh groundwater beneath the floodplain and saline water beneath islands as mentioned above (e.g., McCarthy & Ellery, 1994 Figures 1c and 1d).…”
Section: Critique Of the Jolivet Et Al Modelmentioning
confidence: 99%
See 3 more Smart Citations